Ascorbic acid and CoQ10 ameliorate the reproductive ability of superoxide dismutase 1-deficient female mice. Issue 1 (2nd August 2019) - Ishii, Naoki; Homma, Takujiro; Lee, Jaeyong; Mitsuhashi, Hikaru; Yamada, Ken-ichi; Kimura, Naoko; Yamamoto, Yorihiro; Fujii, and Junichi
Abstract: Superoxide dismutase 1 suppresses oxidative stress within cells by decreasing the levels of superoxide anions. A dysfunction of the ovary and/or an aberrant production of sex hormones are suspected causes for infertility in superoxide dismutase 1-knockout mice. We report on attempts to rescue the infertility in female knockout mice by providing two antioxidants, ascorbic acid and/or coenzyme Q10, as supplements in the drinking water of the knockout mice after weaning and on an investigation of their reproductive ability. On the first parturition, 80% of the untreated knockout mice produced smaller litter sizes compared with wild-type mice (average 2.8 vs 7.3 pups/mouse), and supplementing with these antioxidants failed to improve these litter sizes. However, in the second parturition of the knockout mice, the parturition rate was increased from 18% to 44–75% as the result of the administration of antioxidants. While plasma levels of progesterone at 7.5 days of pregnancy were essentially the same between the wild-type and knockout mice and were not changed by the supplementation of these antioxidants, sizes of corpus luteum cells, which were smaller in the knockout mouse ovaries after the first parturition, were significantly ameliorated in the knockout mouse with the administration of the antioxidants. Moreover, the impaired vasculogenesis in uterus/placenta was also improved by ascorbic acid supplementation. We thus conclude that ascorbic acid and/or coenzyme Q10 are involved in maintaining ovarian and uterus/placenta homeostasis against insults that are augmented during pregnancy and that their use might have positive effects in terms of improving female fertility. Abstract : Summary sentence : The results suggest that antioxidants support fertilizing ability against oxidative stress during parturition.